Antigenic variation during Trypanosoma vivax infections of different host species - Barry, J.D. (Cambridge University Press, 1986)
The sequence of appearance of specific lytic activity against more than 20 variable antigen types (VATs) ofTrypanosoma vivaxin the serum of 27 animals belonging to 5 species has been examined. For each host species there was a characteristic course of infection, with differences in height and duration of parasitaemia and in pathogenicity. The sequence of antigenic variation was similar in all host species, with some VATs consistently eliciting response more rapidly than others. The predominant group, comprising VATs which apparently developed within the first 3 weeks, varied in size according to the total number of trypanosomes in the bloodstream within that period, suggesting there is a spectrum, rather than discrete groupings, in the hierarchy of VAT expression. There was very little evidence for differences in appearance of VATs between host species; the only clear example was one VAT which apparently did not develop in one host species. The sequence of antigenic variation inT. vivaxseems to be determined by the parasite rather than the host species.